PERANAN ELIT DALAM REKONSTRUKSI BUDAYA LOKAL “INGOT-INGOT” DI DESA PANRIBUAN KABUPATEN SIMALUNGUN - Plaza Sembiring, Albret Metro; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika; 2017, 2017)
ABSTRACT   The research was based on the strong position of a group of elite in a village in Karo Tribe called "Simantek kuta". Position is Obtained through elite role when Reconstructing a culture called "Ingot-ingot" meaning returning the favor. The purpose of this research was to know and describe the role of the elite in the reconstruction of the local culture  Ingot-ingot in the village of Panribuan, Simalungun Regency. The theory used is the elite theory and the theory of cultural studies. The methods used by qualitative research. The technique of collecting data through observation, interviews, literature and documentation. This study yields findings where the reconstruction is done by doing a social approach, cultural hegemony and build relations of power in society. The culture of Ingot-ingot is a culture that is very sacred because when a debt of gratitude to appear then this debt is not just a personal debt but also debt into spirit, family debt, and debt of the ancestors, so that if not paid or dibalaskan then it can be a catastrophe. This definition is used by the elite through the power of capital in the form of material wealth and knowledge of the cultural aspects to revive culture of ingot-Ingot in an attempt to menghegemoni the community. Social approach undertaken to understand culture in a diverse community in the Batak tribe. This approach then yields the reconstruction of Ingot-ingots that was built through the existing cultural concept that already exist namely the awarding of "Jabatan" as the Organization of indigenous institutions, the granting of "Marga" as a form of tribal identity and "Perkawinan" in the concept formation of kinship. Elite calculations appear on each value from the third awarding it. On the other hand, the concept of marriage even produce power relations in the system of kinship. Keywords: Role Of The Elites, The Reconstruction Of The Local Culture, Strengthening Power.